CRISS - CROSS HEART (Laporan empat kasus) - Anna Ulfah Rahajoe; Poppy S Roebiono; Muhammad B Fahmi; Ganesja M Harimurti (The Indonesian Heart Association, 2012)
Criss-cross heart is a rare congenital cardiac anomaly characterized by crossing of the inflow streams of the two ventricles. The anomaly seems to be due to abnormal twisting of the heart about its long axis and when the axis of the openings of the atrioventricular valves are not parallel. Thus in criss – cross heart the abnormality is on the atrioventricular relation, not connection, which happened due to clockwise or counter-clockwise ventricular rotation. We report four cases of criss-cross heart, three cases had levocardia - situs solitus with superior – inferior ventricles and one case had dextrocardia - situs inversus (mirror image) the ventricles were not in superior-inferior fashion. Subcostal and apical four-chamber views can be used to identify the ventricular morphology and position, the atrio-ventricular valves, the atrioventricular and ventriculo-arterial connection, and the characteristics of the great vessels. The artery connection can be seen more clearly in the parasternal window. All patients had concordance atrioventricular connection, ventricular septal defect and double outlet right ventricle with malposition of the great arteries. Other associated lesions included infundibular (subvalvular) and valvular pulmonary stenosis in three, atrial septal defect in two, and interrupted aortic arch with large persistent ductus arteriosus in one patient. The findings were confirmed by catheter-ization and angiography in three patients and multislice-CT in one.Conclusions.patients with criss-cross heart can be easily diagnosed by a careful, systematic segmental study with two-dimensional color-coded transthoracic echocardiography. The failure to obtain a characteristic four - chamber view in any cut and the presence of crossed atrioventricular inflow bloodstreams with each atrium draining into the ventricle located contralaterally were diagnostic for recognition of this complex anomaly. The presence of superior-inferior ventricles although suggestive, should not be regarded as diagnostic for criss cross anatomy.